Enabling HIV self-testing in South Africa - M L Richter; W D F Venter; A Gray (Southern African Journal of HIV Medicine, 2012)
In a South African context, we consider the implications of the United States Food and Drug Administration’s recent approval of the OraQuick HIV self-testing kit. We argue that current law and policy inhibit the roll-out of accurate and well-regulated self-testing kits, and create a loophole for sale in supermarkets, but not pharmacies.